Asynchronous telerehabilitation in prehabilitation and postoperative recovery for colorectal cancer: A protocol for a randomized controlled trial - José Manuel Burgos-Bragado; Carolina Jiménez-Sánchez; Natalia Brandín-de la Cruz; Beatriz Carpallo-Porcar; Lilian Le Roux-Ethève; Juan Luis Blas-Laina; Jorge Alamillo-Salas; Paola Gracia Gimeno; Sandra Calvo (PLoS ONE, 2026)
Introduction Colorectal cancer (CRC) is a leading global malignancy, and surgery is frequently followed by complications, functional decline, and reduced quality of life. Multimodal prehabilitation and rehabilitation can improve physical recovery and psychosocial outcomes, but uptake is often limited by logistical and mobility barriers. Asynchronous telerehabilitation offers a flexible, patient - centered, and scalable approach; however, its effectiveness across the perioperative CRC pathway has not been rigorously evaluated. This trial will evaluate a multimodal asynchronous program delivered in prehabilitation and postoperative phases, against a booklet-based usual-care approach reflecting the pre-existing perioperative pathway in the study setting before trial initiation. Methods This single-blind, parallel-group randomized controlled trial will compare an asynchronous multimodal telerehabilitation program with a booklet-based usual-care program in adults scheduled for elective CRC resection. Fifty-six participants will be randomized 1:1 to the telerehabilitation group (HEFORA platform) or the usual-care control group. The intervention includes a 2-week prehabilitation phase and a 4-week postoperative rehabilitation phase. Assessments will be performed at five time points: baseline (pre-prehabilitation), post-prehabilitation (pre-surgery), post-surgery (pre-rehabilitation), post-rehabilitation, and 3-month follow-up. Outcomes The primary outcome is functional capacity, measured by the Six-Minute Walk Test distance. Secondary outcomes include muscle strength, body composition, pulmonary function, physical activity, sleep quality, psychosocial variables, health-related quality of life, treatment expectancy, usability, satisfaction, and adherence. Analyses will follow the intention-to-treat principle using longitudinal models and sensitivity analyses for missing data and adherence. Conclusions: This study will provide evidence on the role of asynchronous telerehabilitation in perioperative colorectal cancer care. Positive results could inform clinical guidelines, promote wider adoption of digital rehabilitation strategies, and support a more accessible, patient-centered, and cost-effective approach to oncologic recovery. Trial registration ClinicalTrials.gov identifier: NCT06593678 .